A Dual Band Slotted Patch Antenna on Dielectric Material Substrate. (28th January 2014) - Habib Ullah, M.; Islam, M. T.; Ahsan, M. R.; Mandeep, J. S.; Misran, N.
Abstract : A low profile, compact dual band slotted patch antenna has been designed using finite element method-based high frequency full-wave electromagnetic simulator. The proposed antenna fabricated using LPKF printed circuit board (PCB) fabrication machine on fiberglass reinforced epoxy polymer resin material substrate and the performance of the prototype has been measured in a standard far-field anechoic measurement chamber. The measured impedance bandwidths of (reflection coefficient < - 10  dB) 12.26% (14.3–16.2 GHZ), 8.24% (17.4–18.9 GHz), and 3.08% (19.2–19.8) have been achieved through the proposed antenna prototype. 5.9 dBi, 3.37 dBi, and 3.32 dBi peak gains have been measured and simulated radiation efficiencies of 80.3%, 81.9%, and 82.5% have been achieved at three resonant frequencies of 15.15 GHz, 18.2 GHz, and 19.5 GHz, respectively. Minimum gain variation, symmetric, and almost steady measured radiation pattern shows that the proposed antenna is suitable for Ku and K band satellite applications.